Survey Manajemen Watersport Salma Dive Shope Centre Di Kepulauan Taman Nasional Karimunjawa (Universitas Negeri Semarang, 2022)
The Management Survey of the Salma Dive Shope Center water sports in the Karimunjawa Islands is a survey of the management of the Salma Dive Shope Center in carrying out sports and recreational activities by utilizing water rides. This study uses quantitative descriptive research methods. Data collection techniques in the form of observation and questionnaires (questionnaires). The data analysis of this research used descriptive questionnaire data processing as a whole resulting from the management of the Salma Dive Shope Center in the Karimunjawa Islands. The results of the study indicate that the management of sports and recreation management carried out by the Salma Dive Shope Center shows that all activities carried out by the Salma Dive Shope Center team have met the safety standards of visitors.